2019
DOI: 10.1002/wer.1220
|View full text |Cite
|
Sign up to set email alerts
|

Response of the photosynthetic activity and biomass of the phytoplankton community to increasing nutrients during cyanobacterial blooms in Meiliang Bay, Lake Taihu

Abstract: Nutrient enrichment facilitates algal outbreaks in eutrophic shallow lakes. To further understand the influence of various inorganic nutrient forms on cyanobacterial blooms, a nitrate (NO 3 ), ammonium (NH 4 ), and orthophosphate (PO 4 ) amendment experiment was conducted in a large shallow lake of China (Lake Taihu) during summer. The results showed that the photosynthetic performance of phytoplankton responded more positively to phosphorus (P) than nitrogen (N), and NH 4 addition stimulated higher algal phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…As a result of these changes, the ratio between the mainly represented taxonomic groups of algae and cyanobacteria, forming the phytoplankton in freshwater basins, has also changed in recent years. It has been reported that cyanobacteria are a dominant group in many water bodies [ 56 , 57 , 58 , 59 , 60 , 61 ]. In some water bodies, there is even a displacement of the Chlorophyta, which traditionally occupy the first place in the phytoplankton of freshwater basins, by representatives of cyanobacteria [ 57 , 60 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these changes, the ratio between the mainly represented taxonomic groups of algae and cyanobacteria, forming the phytoplankton in freshwater basins, has also changed in recent years. It has been reported that cyanobacteria are a dominant group in many water bodies [ 56 , 57 , 58 , 59 , 60 , 61 ]. In some water bodies, there is even a displacement of the Chlorophyta, which traditionally occupy the first place in the phytoplankton of freshwater basins, by representatives of cyanobacteria [ 57 , 60 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cyanobacteria are a dominant group in many water bodies [ 56 , 57 , 58 , 59 , 60 , 61 ]. In some water bodies, there is even a displacement of the Chlorophyta, which traditionally occupy the first place in the phytoplankton of freshwater basins, by representatives of cyanobacteria [ 57 , 60 , 62 ]. In all cases, however, the representatives of these groups of phytoplankton interact with each other and cyanobacteria always have an advantage.…”
Section: Discussionmentioning
confidence: 99%
“…It is a shallow inland eutrophic lake with a maximum depth of 2.6 m and average depth of 1.9 m [57][58][59][60]. It is a drinking water source for more than 40 million people and plays an important role in aquaculture, tourism and flood control [8,58,59]. However, the large population, urbanization, industrial development, intensive agriculture and tourism activities caused hypereutrophic and experienced algal blooms in Lake Taihu since 1990s [61][62][63].…”
Section: Study Areamentioning
confidence: 99%
“…where Pi is the standardized reflectance of one pixel on a single band (Figure 2), Pj is one of the eight spatial neighbors of Pi (Figure 2), Wij is the spatial weight (Figure 2), and n is the number of spatial neighbours (8). Ii is the Local Moran's index that refers to the spatial association between a given pixel (Pi) and its spatial lag variable (∑ ) which was calculated using the spatial neighbors and their corresponding spatial weight.…”
Section: Spatial Autocorrelation Analysismentioning
confidence: 99%
“…Species capable of forming harmful algal blooms can reduce the photosynthetic capacity of coexisting algae by releasing allelochemicals after 10 d of exposure [ 30 ]. In addition, a large amount of N and P can also promote the photosynthesis of algae, which may prolong the duration of algal bloom and cause harm to the aquatic ecosystem [ 31 , 32 ]. The pH can be used as an indirect physicochemical proxy of photosynthesis, because the algae blooms may consume CO 2 faster through photosynthesis than what can be replaced by diffusion and ecosystem respiration.…”
Section: Introductionmentioning
confidence: 99%